Answer:
23
Step-by-step explanation:
(f + g)(3) = f(3) + g(3)
f(3) = 3(3) - 3 = 9 - 3 = 6
g(3) = 4(3) + 5 = 12 + 5 = 17
Then
(f + g)(3) = 6 + 17 = 23
Question 4 options:
18x^4 – 12x^2 = 6x(3x^3 – 2x)
12x^5 + 8x^3 = 2x^3(6x^2 + 4)
20x^3 + 12x^2 = 4x^2(5x + 3)
24x^6 – 18x^5 = 6x^5(4x – 3)
The moon rotates around its axis.
B.
The moon revolves around Earth.
C.
Earth rotates around its axis.
D.
Earth revolves around the sun.
It is because the moon revolves around Earth.
Hope it helps you...
(2n-3)(2n-1), (4p+3)(p+1), (3r-4)(2r-5), (5z-1)(z+4), (2k+3)(k-8), (3t+5)(2t-1), (3x-4)(x+9), (4w+3)(w-2), (2d-7)(2d+5)
these are the answers in order, hope I helped :) please choose my answer as the best xx